IMPACT ANALYSIS OF THE CAPABILITY ON STRATEGY VIA OTHELLO GAME - Jeremy Albert Novaryan; T. Brenda Ch. (Soegijapranata Catholic University, 2014)
Othello is a game that is already antiquated, but the game is still played by many people. Othello game is played by 2 people. If you want to win over the opponent, you must have a good strategy so that all the pieces on the board into the color of the chip.Each player would continue to seek a new strategy to make the pieces multiply. Under these conditions, will result in job terstimulasinya brain to strategize. This of course has an impact on the development of creativity in the organization's strategy.This study was conducted to prove that the game Othello is able to train its player in developing strategies. The results showed that in the Othello game, players are able to train level strategy if he plays continuously. Automatically, playing the game of Othello can stimulate the brain so as to improve the ability to strategize.Keyword Strategic,thinking, critical thinking, tactic